The Strategy of Islamic Religious Education Teacher in Istilling Character Values in Al-Azhar Mandiri Palu Junior High School - Askar Askar; Djazuli Djazuli; Sitti Hasnah (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2022)
This study discusses the strategy of Islamic religious education teachers and manners in instilling character values at Al-Azhar MandiriPalu Junior High School. The formulation of the problem in this study is 1) what are the strategy of Islamic religious education and morals teachers in instilling character values at Al-Azhar MandiriPalu Junior High School? 2) what are the obstacles and solutions provided in instilling character values in Al-Azhar MandiriPalu Junior High School? The objectives of this study are 1) to find out the strategies used by Islamic religious education and morals teachers in instilling character values at Al-Azhar MandiriPalu Junior High School. 2) to explain the constraints and solutions provided in instilling character values in Al-Azhar MandiriPalu Junior High School. This study used a qualitative approach with descriptive informant exposure techniques, and this study used data collection techniques through observation, in-depth interviews and analysis of documentation. Then the data obtained were analyzed using data reduction techniques, data presentation, data verification, and draw conclusions. The results of this study indicate that 1) the strategy used by Islamic religious and moral education teachers in instilling character values ​​both inside and outside the classroom is a) habituation, so that students get used to carrying out the characters being taught, such as discipline, arriving on time at school and others, b) giving advice so that students are motivated and encouraged to do things that the teacher advises during learning, c) set a good example for students with regard to educational values character, d) emphasis strategy, emphasizing doing or applying the material that has been taught in everyday life such as justice and honesty material, e) role-playing, so that students can emulate the role-playing 2) the obstacles faced namely a) some students are spoiled, b) have not been able to understand all students, c) students are less focused on following the lesson learning, d) the network is difficult and long. 3) solutions to overcoming these obstacles include a) taking a personal approach, b) giving a warning to students who make mistakes such as dressing untidy and others, and c) coordinating with class teachers and guidance counsellors in overcoming problems faced by students.